Del Nido versus HTK cardioplegia for myocardial protection during adult complex valve surgery: a retrospective study - Lian Duan; Guo-huang Hu; E. Wang; Cheng-liang Zhang; Ling-jin Huang; Yan-ying Duan (BMC Cardiovascular Disorders, 2021)
Abstract Background Histidine-tryptophan-ketoglutarate (HTK) and del Nido (DN) cardioplegia are intracellular-type and extracellular-type solution respectively, both can provide a long period of myocardial protection with single-dose infusion, but studies comparing the two are rare for adult cardiac surgery. This study aims to evaluate whether DN is suitable for cardioplegia in complex and high-risk valve surgery with long-term cardiac ischemia when compared with HTK. Methods The perioperative records of adult patients infused with DN/HTK as a cardioplegic solution who underwent complex valve surgery with an expected myocardial ischaemic duration longer than 90 min between Oct 2018 and Oct 2019 were analysed retrospectively. Results Of the 160 patients who received DN/HTK and underwent complex valve surgery, we propensity matched 73 pairs. Both groups achieved satisfactory cardiac arrest effects, and no significant difference was found in their cTnI and CK-MB levels within 12 to 72 h postoperatively. The DN group had a higher rate of return to spontaneous rhythm (0.88 v 0.52, P < 0.001), a lower frequency of postoperative severe arrythmias (12% v 26%, P = 0.036), a higher postoperative stroke volume (65 v 59 ml, P = 0.011) and a higher cardiac output (6.0 v 4.9 L/min, P = 0.007) as evaluated by echocardiography, fewer transfusions and shorter ICU stays (both P < 0.05). The two groups had similar inotrope usage and similar incidences of low cardiac output, morbidities and mortality. Subgroup analysis showed that when the aortic clamping time was greater than 120 min, the advantages of DN were weakened. Conclusions DN can be safely applied to complex valve surgery, and it has a similar myocardial protection effect as HTK. Further prospective studies are required to verify these retrospective findings. Trial registration retrospectively registered.